Effect of Blood Component Coatings of Enosseal Implants on Proliferation and Synthetic Activity of Human Osteoblasts and Cytokine Production of Peripheral Blood Mononuclear Cells - Lucie Himmlova; Dana Kubies; Hana Hulejova; Jirina Bartova; Tomas Riedel; Jana Stikarova; Jiri Suttnar; Vlasta Pesakova (Mediators of Inflammation)
The study monitored in vitro early response of connective tissue cells and immunocompetent cells to enosseal implant materials coated by different blood components (serum, activated plasma, and plasma/platelets) to evaluate human osteoblast proliferation and synthetic activity and inflammatory response presented as a cytokine profile of peripheral blood mononuclear cells (PBMCs) under conditions imitating the situation upon implantation. The cells were cultivated on coated Ti-plasma-sprayed (Ti-PS), Ti-etched (Ti-Etch), Ti-hydroxyapatite (Ti-HA), and ZrO2 surfaces. The plasma/platelets coating supported osteoblast proliferation only on osteoconductive Ti-HA and Ti-Etch whereas activated plasma enhanced proliferation on all surfaces. Differentiation (BAP) and IL-8 production remained unchanged or decreased irrespective of the coating and surface; only the serum and plasma/platelets-coated ZrO2 exhibited higher BAP and IL-8 expression. RANKL production increased on serum and activated plasma coatings. PBMCs produced especially cytokines playing role in inflammatory phase of wound healing, that is, IL-6, GRO-α, GRO, ENA-78, IL-8, GM-CSF, EGF, and MCP-1. Cytokine profiles were comparable for all tested surfaces; only ENA-78, IL-8, GM-CSF, and MCP-1 expression depended on materials and coatings. The activated plasma coating led to uniformed surfaces and represented a favorable treatment especially for bioinert Ti-PS and ZrO2 whereas all coatings had no distinctive effect on bioactive Ti-HA and Ti-Etch.